A diffuse argon plume generated downstream of an atmospheric pressure plasma jet equipped with a positively biased electrode. (6th October 2021) - Zhao, Na; Wu, Kaiyue; He, Xingran; Chen, Junyu; Tan, Xin; Wu, Jiacun; Ran, Junxia; Jia, Pengying; Li, Xuechen
Abstract: Compared with the diffuse mode of helium plasma jets, a filamentary mode is normally produced in the plasma plume with less expensive inert gas, such as argon, which is undesirable because intense discharge in the filamentary mode may cause damage to fragile samples. Many efforts have been attempted to realize the diffuse mode of an argon plasma jet. In this paper, the diffuse mode is realized in an atmospheric pressure argon plasma jet with increasing biased voltage ( V b ) applied to a downstream plate electrode. Results show that the diffuse mode transits from the filamentary mode with the increase of V b . Waveforms of voltage, current and integrated light emission reveal that the filament originates from a positive discharge with a needle anode, while the diffuse mode results from negative discharges with a needle cathode, which consist of a Trichel-pulse phase and a slower-varying phase. By fast photography, the positive discharge is attributed to a streamer regime, whereas the negative discharges belong to a Townsend-discharge regime. From optical emission spectroscopy, electron density, electron excitation temperature, vibrational temperature, and rotational temperature are studied as functions of V b .